Thyroid autoimmunity and vitamin D: Effects on in vitro fertilization/intracytoplasmic sperm injection laboratory outcomes - Liu, Yalong; He, Zining; Huang, Ning; Zeng, Lin; Meng, Fangyin; Li, Rong; Chi, Hongbin (Frontiers in Endocrinology, 2022)
This prospective cohort study aimed to determine the effects of TAI, serum/follicular fluid vitamin D levels, and vitamin D receptor expression in granulosa cells on the success of IVF/ICSI. The study included 206 women with or without TAI undergoing IVF/ICSI ovarian stimulation cycles. The primary outcomes were the number of oocytes retrieved and quality of embryos. The secondary outcomes were the association between serum and follicular fluid vitamin D levels and vitamin D receptor expression in granulosa cells. Thyroid autoimmunity was associated with fewer healthy embryos but not oocytes (p = 0.010). In addition, the study populations in the thyroid autoimmunity and non-thyroid autoimmunity groups were divided into two subgroups based on high/low serum/follicular fluid vitamin D levels. There was no significant difference in the number of retrieved oocytes and good-quality embryos between the subgroups with high or low vitamin D levels (p > 0.05). The incidence of thyroid autoimmunity was comparable between the vitamin D subgroups (p > 0.05). The vitamin D level in follicular fluid was significantly correlated with the serum level (p < 0.001, r > 0.5). Linear regression analysis indicated that thyroid autoimmunity had a negative effect on the number of healthy embryos (p = 0.038). RT-PCR analysis demonstrated that vitamin D receptor expression in granulosa cells was positively correlated with follicular fluid vitamin D levels in the thyroid autoimmunity and non-thyroid autoimmunity groups (p > 0.05). The current findings suggest that thyroid autoimmunity may have a more detrimental effect on IVF/ICSI outcomes than vitamin D.